The Intervention of Music Therapy on Adolescent Depression - Yang, Jinglan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The main purpose of this study is to explore the intervention effect of music therapy on adolescent depression, and to summarize and analyze seven related studies, determine intervention effects and characteristics, identify existing problems, and provide suggestions and directions for further research in the future. In summary, the research results indicate that music therapy can effectively alleviate symptoms of depression in adolescents and can be combined with other treatment methods. However, music therapy still has limitations, as its intervention effect on patients with severe depression is relatively small and time limited (long-term use of music therapy treatment will gradually decrease over time). However, there are still inconsistencies between data in existing studies, and the types and methods of treatment used in reference studies are not uniform. Hence, further investigation is required in the future to establish the most optimal timing, frequency, and form of music therapy treatment.